DISPLACEMENT, REHABILITATION AND ENVIRONMENT: विस्थापनए पुनर्वास एवं पर्यावरण - Joshi, Shashi (International Journal of Research -GRANTHAALAYAH, 2015)
Due to the unplanned and uncontrolled use of natural resources and environmental elements for human happiness, prosperity and fulfillment of aspirations, due to this, a situation of environmental disruption and imbalance has arisen. Water, air, land, forests and minerals are constantly decomposing, water sources are drying up, the environment is becoming toxic and land degradation is also happening. The destruction of forests has increased the environmental degradation. Along with all this, an inhuman social problem has arisen and that is the problem of displacement and rehabilitation. The agony of people living close to nature, the problem of inhabiting tribal tribes, the inhuman torture between the desolation of their homes and settling is still unheard of. Baba Amte’s lines expressing his agony are visible. मनुष्य अपनी सुख समृद्धि, भोग एवं महत्वकांक्षाओं की पूर्ति हेतु जिस तरह प्राकृतिक संसाधनों एवं पर्यावरणीय तत्वों का अनियोजित एवं अनियन्त्रित प्रयोग कर रहा है, इस कारण पयावरणीय विघटन एवं असंतुलन की स्थिति उत्पन्न हो गई है। जल, वायु, भूमि, वन एवं खनिज संजीवनी का निरन्तर विघटन हो रहा है, जल स्त्रोत सूख रहे है, वातावरण विषाक्त हो रहा है और भूमि का क्षरण भी हो रहा है। वनों के विनाष से पर्यावरण ह्ास में वृद्धि हुई है। इन सबके के साथ ही एक अमानवीय सामाजिक समस्या उत्पन्न हुई है और वह है विस्थापन और पुनर्वास की समस्या। प्रकृति के नजदीक निवास कर रहे लोगों की व्यथा, आदिवासी जनजातियों के निवास की समस्या, उनके घरों के उजड़ने और बसने के बीच की अमानवीय यातना को झेलने की समस्या अभी तक अनसुनी है। इनकी व्यथा को व्यक्त करती बाबा आमटे की पँक्तियों दृष्टव्य है